Why Breast Cancer Patients Seek Traditional Healers - Mazanah Muhamad; Sharan Merriam; Norhasmilia Suhami (International Journal of Breast Cancer)
Traditional healing is a common practice in low and middle income countries such as Malaysia. Eighty percent of Malaysians consult traditional healers or “bomoh” at some time in their life for health-related issues. The purpose of our study was to explore why breast cancer patients visit traditional healers. This is a qualitative study utilizing in-depth interviews with 11 cancer survivors who sought both traditional and Western medicine. The findings revealed the following reasons for which patients seek traditional healers: (1) recommendation from family and friends, (2) sanction from family, (3) perceived benefit and compatibility, (4) healer credibility, and (5) reservation with Western medicine and system delay. These factors work together and are strongly influenced by the Malaysian cultural context. The issue with the Western health system is common in a developing country with limited health facilities.